2013
DOI: 10.4317/medoral.18042
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the fimA gene in Porphyromonas gingivalis isolated from periodontitis and non-periodontitis patients

Abstract: Objective: The goal of this study was to determine the genetic variability of the fimA gene in Porphyromonas gingivalis isolates from Spanish patients. Study Design: Pooled subgingival samples were taken, processed and cultured in non-selective blood agar medium. Pure cultures of one to six isolates per patient were obtained and PCR and PCR-RFLP were used for fimbrillin gene (fimA) type determination of the extracted genomic (DNA). Results: Two hundred and twenty four Porphyromonas gingivalis isolates from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…FimB modulates fimbrial length and FimC-E are accessory fimbrial proteins (Yoshimura, 1993 ; Watanabe et al, 1996 ; Nishiyama et al, 2007 ; Nagano et al, 2010 ). Based on a PCR typing system, type II has often been associated with disease and with increased virulence in laboratory studies (Amano et al, 1999 ; Fabrizi et al, 2013 ; Feng et al, 2014 ). However, studies using these PCR based typing systems have also shown that type II is the most widely distributed type among both healthy subjects as well as those with periodontitis (Moon et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…FimB modulates fimbrial length and FimC-E are accessory fimbrial proteins (Yoshimura, 1993 ; Watanabe et al, 1996 ; Nishiyama et al, 2007 ; Nagano et al, 2010 ). Based on a PCR typing system, type II has often been associated with disease and with increased virulence in laboratory studies (Amano et al, 1999 ; Fabrizi et al, 2013 ; Feng et al, 2014 ). However, studies using these PCR based typing systems have also shown that type II is the most widely distributed type among both healthy subjects as well as those with periodontitis (Moon et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the nucleotide variation, fimbriae are classified into six genotypes (type I, Ib, II, III, IV and V), and are encoded by the fimA gene [9]. Studies have been carried out to examine the presence of these genotypes in different geographical locations and ethnic groups to investigate the relationship between the fimA genotype and disease severity [9][10][11][12][13][14][15]. In Japanese adults, types II and IV have been found to be more prevalent in periodontitis patients, whereas type I has been associated with healthy individuals [9].…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente nuestros resultados muestran una asociación entre la detección del genotipo fimA IV y la presencia de periodontitis crónica severa, coincidiendo con los resultados reportados en otros países (20,29,30) . Sin embargo, nuestro estudio contrasta con los datos de otras poblaciones en los que el genotipo más frecuente sería el fimA II (11,13,14,20,21,31,32) . Estas variaciones pueden ser atribuidas a patrones étnicos y / o geográficos particulares (11,14) .…”
Section: Discussionunclassified